Structural assessment and characterization of the unstable rock slopes at Mellomfjellet, Nordreisa - Vik, Bernt Kristian Flekstad (UiT Norges arktiske universitet, 2019)
The aim of this study has been to structurally assess and characterize the unstable rock slopes (URS) at Mellomfjellet using an interdisciplinary approach of structural geological analysis, geomorphological mapping, photogrammetry and remote sensing. The URS are located on the west-facing slopes of Mellomfjellet and display a dramatic geomorphology with deep ice filled fractures and clearly displaced blocks in the glacially eroded Reisadalen in Northern Troms. Geological mapping of Mellomfjellet showed that the bedrock consists predominantly of amphibolite. The area was divided into two domains (MF1 and MF2) where MF1 comprised of a foliation (strike/dip; 169°/15°±18.9°) and three joint sets: J1 (029°/72°±16. 3°), J2 (286°/83°±21.8°) and J3 (075°/67°±12.3°). MF2 comprised of a foliation (183°/11°±14.3°) and three joint sets: J1 (022°/82°±14.7°), J2 (108°/88°±15.3°) J3 and (071°/52°±12.7°). Joint set J3 was for both domains found in relation to two E – W-trending morphological depressions. The mapped joint sets correlated well with joint sets determined from drone photogrammetry, and InSAR displacement showed structural trends, delineated by mapped bedrock structures and morphological elements. The kinematic analysis from MF1 showed that flexural toppling along J1 was a partly feasible failure mechanism. Planar failure along the foliation was feasible for some of the foliation and therefore a bi-planar compound slide comprising of J1 and the foliation is proposed as the main failure mechanism. At MF2 flexural toppling along J1 is the main failure mechanism and slide topple is proposed, as there is feasibility for planar sliding along some of the foliation. The mapped bedrock structures align with regional structural geological trends and are interpreted to govern the failure mechanisms and delineation of the URS at Mellomfjellet. Worst-case scenarios for each domain where delineated based on geomorphological features in order to assess consequences connected to the URS. The scenarios ranged from 1 to 3 Mm3 in ...